Compensation of the losses caused by unfair competition: national and foreign legal approaches - Maskayeva, Natallia G. (Journal of the Belarusian State University. International Relations, 2018)
The article is devoted to the approaches to regulation in the Republic of Belarus and foreign countries of the compensation of the losses caused by unfair competition. The author considers, in particular, such issues as the kinds of the recoverable losses, the range of the persons entitled to their compensation, and the persons against whom the corresponding claim may be brought, the conditions of the compensation of the mentioned losses etc. Based on the analysis made the need for the Regulation of the Plenum of the Supreme Court of the Republic of Belarus concerning the recognition and enforcement in the Republic of Belarus of foreign judgments and arbitration awards on recovery of punitive damages, as well as the amendment of the national legislation, allowing compensation of the losses caused by unfair competition, in case of failure to prove their exact size, is substantiated.
Keywords: unfair competition; measures of civil liability; compensation of losses; real damage; lost advantage; punitive damages